Development of Chemis 3D Augmented Reality Media for Discovery Learning Model in Chemical Bonding - Sahrawati, Fiska; Danial, Muhammad; Salempa, Pince; Djangi, Muhammad Jasri (Hydrogen: Jurnal Kependidikan Kimia, 2024)
The goal of this research and development (R&D) study was to develop a 3D Chemis media product that included cards and applications for three-dimensional display. The 4-D development model by Thiagarajan et al., which comprised the phases of defining, designing, developing, and distributing, was consulted in the creation of this 3D chemistry media. The study's findings included the following: 1) two media experts and two material experts' evaluations of the media's viability and validity fell into the extremely valid group; 2) During the limited testing phase, which involved 29 students from class X MIA 5 SMAN 16 Makassar, each student received an average learning outcome test score of 83.3 out of 100, with 86.2% of the class completing the course. Additionally, the evaluation of student motivation for this media fell into the very high category, suggesting that the media was effective; 3) both students' and teachers' responses to the developed learning media fell into the very high category, suggesting that the media was useful. Following a validation stage by experts and validators, development revisions, and a small number of trials, this learning material was found to be reliable, useful, and efficient. The Chemis 3D media model was shown to be reliable, useful, and efficient.